Palaeotectonic environment and landslide phenomena in the area of Malakasa, Greece. - Mourtzas, N. D.; Sotiropoulos, E. (Bulletin of the Geological Society of Greece, 2013)
The extended landslide of Malakasa area, located 35km to the North of Athens, occurred in a neopalaeozoic schist-sandstone klippe, a complex Palaeotectonic environment in the northern roots of Parnitha Mt. Due to this failure, railway line and highway connection between Athens and central and North Greece were cut off. In this paper, it is attempted to approach the landslide mechanism based on: (i) the kinematic data on the failure surface, (ii) the morphological features of the surface, (iii) the movement vectors, and (iv) the lithostratigraphy and hydro-geological features of the sliding mass. According to the above criteria, three soil blocks can be identified in the landslide mass, which are differentiated by their lithological structure, kinematic features, type of deformation and hydro-geological behavior. The causal factor of the extended landslide was the gradual loss of support of these three blocks and their slide on a pre-sheared surface of low strength that has been caused by the extended excavation in the slope toe. The palaeotectonic structure and the development and geometry of the geological formations in the landslide area were not taken into account during the construction of the drainage works, for slope stabilization and the increasing of safety factor, something which led to the over-designing of the remedial measures.